DRY MATTER PRODUCTION, CARBOHYDRATE RESERVE CONTENT AND NITROGEN UTILIZATION IN SOME TROPICAL GRASSES AS INFLUENCED BY NITROGEN FERTILIZATION AND AGE OF PLANTS - . Rusdy (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2010)
An experiment was conducted at Kyushu University Experimental Field Japan, to evaluate the effect of nitrogen fertilization and cutting age on dry mater yield, reserve carbohydrate content and nitrogen utilization in alang-alang, bahia grass and guinea grass. The grasses species were fertilized with 0. 7 and 1.5 g N/pot and cut at 50 and 70 days after nitrogen fertilization. Results of the experiment showed that as nitrogen rates increased, dry matter yield, foliage (stubble + underground parts) ratio, nitrogen concentration and nitrogen uptake of the three species increased. Alang-alang allocated a greater proportion of dry matter to stubble and underground plant parts than to foliage compared to those of bahia grass and guinea grass. Nitrogen fertilization had no consistent effect on reserve carbohydrate content, apparent nitrogen recovery and nitrogen use efficiency. Cutting at 70 days increased dry matter yield and nitrogen uptake but reduced nitrogen concentration of the three grass species. As plant grew older, foliage (stubble + underground parts) ratio decreased in alang-alang but in bahia grass and guinea grass it increased. Alang-alang was less responsive to applied nitrogen in term of nitrogen uptake compared with those of bahia grass and guinea grass, however as the plants grew older, guinea grass showed the highest nitrogen use efficiency compared with those of alang-alang and bahia grass.